Pengaturan Pemutusan Hubungan Kerja (Phk) di Indonesia dan Singapura: Studi Perbandingan Hukum Indonesia dan Hukum Singapura - Haikal Sudjudiman; Fatma Ulfatun Najicha (UIR Press, 2020)
As a rule of law, Indonesia is required to provide legal protection to all its citizens, including employers and workers. Legal protection for workers to ensure the basic rights of workers to create workers' welfare, including termination of employment. However, in practice, there are still cases of rights in terms of termination of employment. This journal will describe clearly the equality and guarantee of legal protection for workers' rights in cases of termination of employment in Indonesia and Singapore so that we can benefit from the legal protection offered by Singapore. This research is a juridical normative legal research using the comparative law method. Therefore, the data source used is a secondary data source collected by literature study techniques. After the data is collected, the data is processed and analyzed using descriptive qualitative analytic methods, meaning that the data is grouped according to the aspects studied and then drawn from the conclusions and described descriptively. Based on the research results, it is found that the legal protection of the rights of daily workers in Indonesia and Singapore has its own advantages and disadvantages.